2008
DOI: 10.1177/0021998308092196
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Yttria-doping on Mechanical Properties of Bovine Hydroxyapatite (BHA)

Abstract: Sintered bodies of hydroxyapatite, derived from calcinated bovine bone (BHA) and doped with 0.5 and 1 wt% Y2O3, were prepared. Measurements of density, compression strength, and microhardness, along with scanning electron microscopy (SEM) and X-ray diffraction (XRD) were carried out. The experimental results showed that BHA doping with yttria favors formation of glassy phase, which advances sintering and results in a dense and reinforced BHA matrix. The best mechanical properties were achieved after sintering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
(24 reference statements)
1
9
1
Order By: Relevance
“…The microhardness of sintered pure HA with biological (bovine) origin (BHA) was measured in our earlier study as 145 HV for samples sintered at 1300°C, which is considerably lower than the values found in this study. Many researchers have tried to reinforce HA.…”
Section: Resultscontrasting
confidence: 78%
See 4 more Smart Citations
“…The microhardness of sintered pure HA with biological (bovine) origin (BHA) was measured in our earlier study as 145 HV for samples sintered at 1300°C, which is considerably lower than the values found in this study. Many researchers have tried to reinforce HA.…”
Section: Resultscontrasting
confidence: 78%
“…The peaks of β‐TCP (beta tricalcium phosphate) are also observed in the X‐ray diffractograms at 1300°C, attributed to the partial decomposition of HA to β‐TCP, which usually occurs in synthetic HA at temperatures above 1200°C . The resistance of HA to extensively transform to β‐TCP even at 1300°C in this study is attributed to the biological origin of HA, which has been observed many times in our previous studies . However, it is worthy of noting that this thermal resistance was not annulled by the presence of h‐BN in the matrix of HA.…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations